Artificial intelligence-driven personalization for dietary and physical activity interventions: a systematic review of chatbot efficacy, design characteristics, and methodological quality - Rizal, Akhmal; Sazali, Razif; Md Yusoff, Yusandra; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This systematic review evaluates the effectiveness and design quality of AI-driven conversational agents in promoting physical activity, healthy diet, and weight management among adults. By searching major databases through January 2025 and screening English-language studies including RCTs and quasi-experimental designs the research appraises chatbot features, theoretical frameworks, and methodological rigor using tools like Cochrane RoB 2 and GRADE. The study addresses existing gaps in fragmented literature by synthesizing how specific conversational elements and intervention durations influence lifestyle outcomes, ultimately providing a standardized framework to inform the development of future AI-powered health coaching interventions.